Peran BK Dalam Meningkatkan Gaya Belajar Siswa - Aristi, Dedearisti; Wahyu Hidayati, Novi; Sulistiawan, Hendra (Universitas Palangka Raya, 2024)
This study aims to determine the learning style of class XI students at State Senior High School 1 Semparuk, Sambas Regency, The method used is quantitative descriptive method. The data collection tools are, interview mix, psychological scale and documentation. The population in this study were all students of class XI IPS State Senior High School 1 Semparuk Sambas Regency with a population of 167 students with a research sample of 40 students. From the data that has been collected and then arranged and described objectively in the form of a narrative, it obtained an average percentage of 68.25% with the category